BS5 Diabetic cardiomyopathy is associated with loss of endothelial glycocalyx in coronary microvessels and angiopoietin 1 restores endothelial glycocalyx and corrects cardiac function. (May 2019) - Qiu, Yan; Ramnath, Raina; Jenner, Sophie; Fawaz, Sarah; Arkill, Kenton; Neal, Chris; Verkade, Paul; White, Stephen; Salmon, Andrew; Suleiman, M.-Saadeh; Welsh, Gavin; Foster, Rebecca; et al.
Abstract : Introduction: Endothelial glycocalyx (eGlx) contributes to the microvascular permeability barrier and its dysfunction correlates with albuminuria in diabetic nephropathy. Albuminuria is a potent risk factor for cardiovascular disease. We therefore hypothesised that coronary microvascular eGlx damage also occurs in diabetic cardiomyopathy (DCM). Methods: Diabetes was induced in FVB mice with streptozotocin (STZ). DCM was assessed with echocardiography by E/A ratio. A group of diabetic FVB mice received Angiopoietin 1 (Ang1) after DCM development. Results: FVB mice developed DCM at 7 weeks post STZ injection. Labelling with MAL-I, a specific lectin that binds to eGlx, was reduced in diabetic heart capillaries (DCM vs. ctrl: 1.64±0.27 vs. 2.70±0.27). Electron microscopy of diabetic heart capillaries showed decreased eGlx depth (DCM vs. ctrl: 14.54±0.79 vs. 27.88±5.82nm), increased perivascular space (DCM vs. ctrl: 2.08±0.22 vs. 0.54±0.11fold) and thickened endothelial cells (DCM vs. ctrl: 0.30±0.04 vs. 0.22±0.01μm). Partial depletion of eGlx in rat hearts with the combination of heparanase and chondroitinase led to decreased cardiac output (enzymes vs. ctrl: 63.47±10.14% vs. 91.68±9.82%). Ang1 improved diastolic function of FVB mice with DCM (DCM vs. DCM+Ang1: 1.05±0.08 vs. 1.35±0.09 fold relative to pre-treatment). In Ang1-treated diabetic mice, eGlx thickness in heart capillaries (DCM vs. DCM+Ang1: 13.87±0.87 vs. 24.55±2.02nm) and eGlx coverage (DCM vs. DCM+Ang1: 48.08±3.07% vs. 82.44±5.43%) were improved, and the increased perivascular space due to oedema in DCM normalised (DCM vs. DCM+Ang1: 2.08±0.13 vs. 0.23±0.03fold). Conclusion: We have shown DCM development is associated with eGlx damage and that injury to eGlx impairs cardiac function. Recovered heart function with Ang1 treatment parallels reversal of eGlx loss. As such, correction of eGlx damage may have therapeutic potential for DCM and other diabetic vascular complications. Conflict of interest: None